Factores de riesgos asociados a la Multidrogorresistencia en pacientes con diagnóstico de Tuberculosis Pulmonar en el Distrito de Salud 02d04 Caluma – Echeandía – las naves, 2022. - Silva Coloma, Adriana Lizbeth (2022)
The present investigation deals with the risk factors associated with multidrug resistance in patients diagnosed with pulmonary tuberculosis in the Caluma - Echeandía - Las Naves Health District, 2022, it aims to identify the main risk factors that influenced the appearance of the multi-drug resistance within the health entities that make up the aforementioned district; the same as through a viable methodological framework that had a descriptive, bibliographic, field level and a non-experimental, cross-sectional, retrospective and quantitative design where the data were collected in person from a sample of thirteen patients, eleven of whom diagnosed with sensitive and two multidrug-resistant pulmonary tuberculosis through an applied survey using a questionnaire as an instrument; Once the information had been processed, the need to create active environments for the culture of prevention on the risk factors of multidrug resistance became evident; Therefore, training was implemented for patients with this condition in order to strengthen both theoretical and practical knowledge on fundamental issues of the disease such as: diagnosis, control, monitoring, and effective treatments to help improve quality. of life and therefore comprehensive health. Keywords: Pulmonary tuberculosis, multidrug resistance, risk factors, preventive strategies.